Crystalline hydrogenation of graphene by scanning tunneling microscope tip-induced field dissociation of H2. (November 2017) - Tjung, S.J.; Hollen, S.M.; Gambrel, G.A.; Santagata, N.M.; Johnston-Halperin, E.; Gupta, J.A.
Abstract: We have developed a novel method for crystalline hydrogenation of graphene on the nanoscale. Molecular hydrogen was physisorbed at 5 K onto pristine graphene islands grown on Cu(111) in ultrahigh vacuum. Field emission local to the tip of a scanning tunneling microscope dissociates H2 and results in hydrogenated graphene. At lower coverage, isolated point defects are found on the graphene and are attributed to chemisorbed H on top and bottom surfaces. Repeated H2 exposure and field emission yielded patches and then complete coverage of a crystalline √3 × √3 R30° phase, as well as less densely packed 3 × 3 and 4 × 4 structures. The hydrogenation can be reversed by imaging with higher bias voltage. Graphical abstract: